Trauma to the gallbladder is associated with concurrent injuries to the extra hepatic biliary system: A South African experience. Issue 1 (January 2022) - Kong, Victor; Xu, William; Cheung, Cynthia; Rajaretnam, Nigel; Elsabagh, Abdalla; Dholakia, Jhanvi; Bruce, John; Laing, Grant; Manchev, Vassil; Clarke, Damian
Highlights: Gallbladder injury is rare but when encountered implies a significant degree of trauma. We present the largest gallbladder injury series to date. Cholecystectomy is usually definitive, and outcomes are often determined by associated injuries rather than the gallbladder injury itself. Abstract: Introduction: Gallbladder trauma is a rare injury. This study aimed to describe the significance of these injuries and the appropriate management strategies. Methods: A retrospective study was undertaken at a major trauma centre in South Africa and included all patients diagnosed with a gallbladder injury between January 2012 and October 2020. Results: A total of 51 cases were included (88% male, mean age: 38 years), with 44 (86%) penetrating trauma cases [28 stab wounds (SW), 16 sustained gunshot wounds (GSW)]. Of the 7 (13%) blunt trauma cases, five were involved in a motor vehicle crash, and two were injured via assault. All patients underwent laparotomy. Full-thickness gallbladder laceration or perforation was the most common type of injury (84%) and all patients with a gallbladder perforation or laceration had a cholecystectomy at index operation. Two out of 5 patients with a gallbladder contusion were managed conservatively without a cholecystectomy and the remaining three had evidence of gallbladder necrosis which were managed with cholecystectomy. Associated extrahepatic bile duct injuries occurred in 4% of cases, and 18 cases (35%) required intensive care unit (ICU) admission. The overall mortality was 8%. Conclusion: Gallbladder injury is rare but when encountered implies a significant degree of trauma. Although cholecystectomy is usually definitive, there is an association with other occult extra-hepatic biliary tract injuries. The severity of the associated injuries usually determines patient outcomes.